Between Policy and Reality: Gendered Gaps in Accessing Social Welfare Services in Zanzibar and Indonesia - Faki, Bakari Khatib (PT. Riset Press International, 2026)
The social welfare expansions have emerged as the major axis of the global south agendas to poverty reduction and gender equality. Regardless of the progressive policy promises, the translation of these intentions into fair access is not even theorized. Current literature seems to focus more on policy design and coverage indicators, creating a significant gap in the literature regarding the role of gender and its influence on access in the day-to-day implementation of access, especially in comparative settings. This study fills this gap by examining the gendered access to social welfare services in Zanzibar and Indonesia. It seeks to examine mediating roles of policy promises to inclusion and the functioning of gender through policy processes. The research design is a qualitative comparative design methodology that involves secondary data, such as policy documents, administrative reports, and existing empirical studies. The discussion will be driven by a unified model that involves Feminist Social Policy Theory and Street-Level Bureaucracy. The findings from a qualitative analysis of policy texts, program reports, and existing empirical studies indicate that the inclusion of women is habitually mediated by care burdens, documentation inequalities, and frontline interpretations of deservingness. Consequently, policy promises tend to deliver differentiated and delayed results. It is by foregrounding such mechanisms that the study contributes to current discourses on welfare governance at the international level and emphasizes the necessity of revising implementation practices and legislative ambition.